Solvent swelling and pre-heating on sub-bituminous Malaysian coals - the effect on coal thermal stability and microstructure / Assoc. Prof. Dr. Hj. Khudzir Hj. Ismail and Mohd Azlan Mohd Ishak - Ismail (Hj.), Khudzir (Assoc. Prof. Dr. Hj.); Mohd Ishak, Mohd Azlan (2006)
Swelling properties of Mukah Balingian coal with various H-bonding (i.e. pyridine, THF, acetone, ethanol and methanol), non-hydrogen bonding (i.e. tetralin, hexane and toluene) were investigated using volumetric swelling ratio method. A higher rank Silantek coal was used as a comparison study. Besides, the swelling properties on to the pre-heated treated coal samples at 100 and 200 °C also been investigated. In all cases, H-bonding solvents exhibit higher swelling ratio in the coal than the non-H-bonding solvents with pyridine being the best swelling solvent. Swelling ratio of MB coal in all solvents gave higher values than SL coal due to low cross-link density and smaller size of aromatic ring cluster that exhibit in low rank coal. In addition, the swelling ratios of the MB coal with mixed of tetralin with the other H-bonding solvents at volume ratio of 20:80, 40:60, 60:40 and 80:20 were decreased with increased in the volume ratios of tetralin. This is probably attributed to the less interaction of the coal reactive sites with the solvent due to its non-hydrogen bonding characteristics. A high swelling ratio however also being observed with the pre-heated coal samples at 100 °C whereas the swelling ratios were decreased for pre-heated coal at 200 °C. An increase in the swelling ratio for pre-heated coals at 100 °C indicates that heat treatment had caused a decrease in the apparent cross-link density with an increased in open structure of the coal macro structure. Furthermore, the thermal behaviour of pre-swelled, pre-heated and preheated swelled samples that were represented by DTG curve showed some changes on coal macrostructure had occurred during pre-treatment processes. In general, the overall activation energy and pre-exponential factor of all pre-treated samples at second stage pyrolysis (i.e. 200 to 700 °C) that were determined using the first-order kinetic reaction model showed lower values in comparison to the untreated coal due to the bond weakening of the coal macromolecular interaction network of the former. Interestingly, in all cases, the mixed solvent swelled samples exhibit much lower activation energy and higher organic volatile matter in comparison to untreated and pure solvent-swelled coal samples indicating an increased in reactivity of the coal during swelling. In addition, the MB pre-heated pyridine-swelled sample showed a further decrement in activation energy indicating an event weakened of the coal-coal macromolecular interactions with less energy being required during the pyrolysis process. The coal macrostructure of the swelled MB coal samples showed some changes when swelled with H-bonding solvents as showed through SEM micrographs where the swelled coal appeared to be more porous and brittle with the surfaces were being plain and smooth. The coal microstructure also showed some glueing and plastic deformation with formation of smaller particles due to the pores improvement during swelling pre-treatment process. Hence, pre-swelling treatment might give a future approach in increasing coal conversion and oil yield during coal liquefaction processes at less severe condition.